2013
DOI: 10.1002/ajmg.a.36134
|View full text |Cite
|
Sign up to set email alerts
|

A novel SOX9 H169Q mutation in a family with overlapping phenotype of mild campomelic dysplasia and small patella syndrome

Abstract: The phenotypic similarities have been demonstrated between non-lethal campomelic dysplasia (CD) and small patella syndrome (SPS), in which different genetic defects have been identified. We report on a familial case of skeletal dysplasia with overlapping phenotype of mild CD and SPS, including defective ischio-pubic ossification, elongated femoral neck, hypoplastic patellae, and increased space between the first and the second toes (sandal gap). Direct sequencing analysis demonstrated a novel missense mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
0
18
0
4
Order By: Relevance
“…The range of functions that Sox proteins serve is broad, including maintaining stem cell features, restricting lineage, and directing terminal differentiation. Germline SOX9 heterozygous inactivating missense and nonsense mutations result in campomelic dysplasia, a syndrome resulting in skeletal malformations, central nervous system dysfunction, as well as abnormalities in other organs [12]. …”
Section: Introductionmentioning
confidence: 99%
“…The range of functions that Sox proteins serve is broad, including maintaining stem cell features, restricting lineage, and directing terminal differentiation. Germline SOX9 heterozygous inactivating missense and nonsense mutations result in campomelic dysplasia, a syndrome resulting in skeletal malformations, central nervous system dysfunction, as well as abnormalities in other organs [12]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite this large number of reported SOX9 mutations in ACD, the functional consequences of these mutations have only occasionally been tested experimentally. For five missense mutations, four in the HMG domain (M113V, R152P, H165Q, and H169Q) and one in the dimerization domain (A76E), residual DNA-binding (Meyer et al 1997) and also transactivation of SOX9 target genes has been demonstrated (Sock et al 2003;Staffler et al 2010;Matsushita et al 2013). Pop et al (2005) studied a cohort of 10 CD cases, including several cases with longer survival and two ACD cases, which were all heterozygous for the nonsense mutation Y440X that truncates the C-terminal transactivation domain spanning residues 402-509 of SOX9.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding chromosomal rearrangements, to our knowledge nine SOX9 missense mutations [Friedrich et al, 2000;Thong et al, 2000;Moog et al, 2001;Sock et al, 2003;Michel-Calemard et al, 2004;Wada et al, 2009;Staffler et al, 2010;Matsushita et al, 2013] and one insertion causing frameshift [Beaulieu Bergeron et al, 2009] have been detected in patients with acampomelic campomelic dysplasia. The missense mutation c.316A>G (p.Lys106Glu) detected in our patient has not been reported previously as causing acampomelic campomelic dysplasia.…”
Section: To the Editormentioning
confidence: 94%